The woman who wore a badge [large type] - Crigger, C. K. (Crigger, C. K. Woman who, 2023)
"January Billings is starting over after bringing her husband's murderer to justice when a stranger shows up at her ranch door. The sheriff, weaseling out of his duties, has sent Eli Pasco to enlist January's help in recovering a horse that's been stolen from him by a young girl. Eli hadn't expected the deputy to be a woman, and he's none too pleased with having to deal with her. Even so, they set out to find the girl and his horse. It isn't long before they discover that, rather than a thief, they're looking for a kidnapped girl. With the outlaws aware they're being pursued, first January, then Eli is caught in a trap. The outlaws leave Eli for dead, and January is left in the hands of a mad killer. Tough, wily, and strong, she manages to get free. Determined to save Zora, she follows the outlaws. Meanwhile, Eli, confused as to which trail to follow, has gone after his horse. Crossing the mountains, they all wind up on the coast. January and Eli will have a final shoot-out before the girl is rescued, the outlaws either killed or captured, and January is left with a new decision to make..." -- Provided by publisher.